LEGAL REVIEW OF MARRIAGE ITSBAT TO DETERMINEORIGIN OF CHILDREN - Sixson (PT. Lembaga Penerbit Penelitian Nusantara, 2025)
The provisions of Marriage and positive law in Islam are designed to validate marriages conducted without proper evidence as provided by Marriage Law No. 1 of 1974. The reason for the isbat of marriage. can be done by showing that the marriage was conducted before the marriage certificate, or it can be done for reasons such as the loss of the marriage certificate or marriage record, confirming the child's status for divorce and inheritance, and many more. The marriage process to determine the child's guardian in the study of Islamic law and positive law is carried out after the trial judge receives the application and examines the requested materials and hears the witnesses. The opinion of the scholar Abdullah Ali Husein and the fiqh experts regarding the itsbat of marriage to determine the parentage of a child if it is not intended for marriage, then A child is called an illegitimate child. This is related to the legal rights received by children from their parents. Illegitimate offspring have a civil relationship only with the mother and the mother's family.